"That's where my money goes": resource production and financial flows in the Yukon economy. Issue 1 (2nd January 2016) - Huskey, Lee; Southcott, Chris
Abstract: Staple theory is offered as an alternative to the resource curse for discussing resource development and sustainability in Northern regions and communities. Staple theory examines the money flows from resource development along the backward, forward, fiscal and final demand linkages to the local economy. Staple theory provides for more specific types of policy recommendations for affected communities. The staples approach is applied to the Canadian Yukon. A general overview of the Yukon's historic resource development is presented. This is followed by an application of the staples approach to the recent Yukon resource boom.